EU og arbejdspladsromanen: Landbrug og bureaukrati hos Robert Menasse og Michel Houellebecq - Kjærgård, Jonas Ross (Passage - Tidsskrift for litteratur og kritik, 2020)
The article presents a comparative analysis of two contemporary EU novels, Robert Menasse’s Die Hauptstadt (2017) and Michel Houellebecq’s Sérotonine (2019). Based on the observation that both novels investigate the bureaucracy of the EU and the changing framework conditions of European farmers, this article argues that Menasse and Houellebecq present a peculiar EU power distribution that can be summed up in the formula sovereignty without a sovereign. In investigating the dynamics of this distribution, the novels are shown to combine elements from various novelistic genres, including the proletarian novel, the picaresque and the multiperspectival novel.